Diversity, community structure and conservation status of an Atlantic Forest fragment in Rio de Janeiro State, Brazil - Cysneiros, Vinicius Costa; Mendonça-Junior, Joaquim de Oliveira; Gaui, Tatiana Dias; Braz, Denise Monte (Biota Neotropica, 2015)
The State of Rio de Janeiro still holds unknown portions of the Atlantic Forest, which represent gaps in the knowledge of this ecosystem. Paracambi and neighbor municipal districts comprise a vast stretch of virtually unknown forest that makes up part of the Serra do Mar biodiversity corridor. The following study describes the tree community structure in a stretch of the ombrophilous Atlantic Forest, in the Parque Natural Municipal do Curió (Curio MNP), Paracambi, Rio de Janeiro, which serves as the basis to evaluate species diversity and conservation status. The altitudes in the area ranges from 100 to 690 m and the climate varies from mild subtropical to tropical hot and humid. Forty plots (10x10m) were randomly placed along the area, where all the stems equal to or greater than five centimeters (5 cm) diameter at breast high from ground level were measured. A total of 749 individuals, pertaining to 128 genera and 210 species were recorded, eight of which are listed as threatened of extinction in the Brazilian flora. The Shannon-Weaver diversity index (H′) was 4.7 nat.ind.-1 and the species with greater importance value was Pseudopiptadenia contorta (1.6460 m2; 18 individuals) while the most common species wereSenefeldera vertcilata (48) and Actinostemon verticilatus (47 individuals). Despite the sample area being a little smaller than that commonly adopted in tropical studies, data pointed to a richness hitherto not registered in any other study for the State of Rio de Janeiro, no matter the inclusion criteria used, and also confirmed by the two estimator indices used, which have revealed very similar results. The vertical forest structure, the values associated to the successional stage of the species and other aspects of community structure indicate that the Curio MNP encompasses forest stretches in advanced stages of ecological succession. Besides its key location for the connectivity of forest fragments in the region, the results emphasize the ecological importance of this forest remnant and the need for its conservation.